MMSA: Metamodel Multimedia Software Architecture. (20th July 2010) - Derdour, Makhlouf; Roose, Philippe; Dalmau, Marc; Ghoualmi Zine, Nacéra; Alti, Adel
Abstract : Interoperability explains how two or more systems or components exchange and process information. The heterogeneity communication mechanisms of the components (GPRS, WIFI, Bluetooth, ZigBee, etc.), transmission speed, as well as the variety of the media (sound, video, text, and image) they manage have a strong influence on the interoperability. That requires the management of the adaptation to an abstract level in order to avoid ad hoc nonreusable, and/or generalizable solutions. In this paper we propose a metamodel for architectures with heterogeneous multimedia components. It enables the description of the software architectures as a collection of components manipulating various types and formats of data, and interacting between them via specific adaptation connectors.